Juris et de jure : paradigma perundangan dalam pembangunan masyarakat - Ahmad Shamsul Abd. Aziz (Penerbit Universiti Utara Malaysia, 2004)
Legal issues referred to development of laws and its impact on Malaysian society; collection of articles